Silk fibroin / hydroxyapatite composite material, its manufacturing method and use
Patent Information
- Application Number
- JP2023561046
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-20
- Filing Date
- 2022-03-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-03-09
AI Technical Summary
【0020】 従来技術と比較して、本発明は、以下の利点及び有益な効果を有する。 (1)本発明で製造された水酸燐灰石/シルクフィブロイン複合材料(nHA/SF)は、長さが150mmにも達する骨釘を製造することができ、その三点曲げ最大ひずみ応力は、171.73Nに達することができ、引張破断強度は、112.2MPaに達することができ、曲げ強度及び引張破断強度は、どちらも同仕様のPLA骨釘を大きく上回っており、従来の水酸燐灰石/シルクフィブロイン複合材料が4mmよりも長い骨釘を製造できないとの問題を解決した。 (2)本発明で製造された水酸燐灰石/シルクフィブロイン複合材料(nHA/SF)には、直径が2~10μmで、形状が規則的な孔隙が存在し、骨細胞がこれらの孔隙内で成長することができ、材料の分解及び骨細胞の成長に伴って、この孔隙はさらに大きくなり、より多くの骨細胞がそこで成長することができ、骨誘導性が顕著である。
Smart Images

Figure 0007635423000002 
Figure 0007635423000003 
Figure 0007635423000004
Abstract
Description
[Technical field]
[0001] The present invention belongs to the technical fields of material science and clinical medicine, and relates to a silk fibroin / hydroxyapatite composite material, its preparation method and its use. [Background technology]
[0002] Fracture refers to partial or complete interruption or loss of integrity or continuity of bone or cartilage tissue when the bone or cartilage tissue is subjected to violent action, and deformation, dysfunction and abnormal activity are typical symptoms of the disease. Patients with severe fractures may develop complications such as shock, which may be life-threatening. Treatment is usually performed by surgically implanting a fracture fixation material. An ideal bone repair material should have the following properties: (1) Biocompatibility: It can directly bond with bone without interfering with the normal activity of bone cells on the surface or the natural regenerative activity of surrounding bone cells. (2) Mechanical resistance: The compressive elastic modulus of human cortical bone material should be at least 45 MPa or more. (3) Biodegradability: It can be automatically decomposed after a certain period of time in the human body and metabolized in the host's body, and does not need to be removed by a secondary operation. (4) Guided regeneration: It stimulates or induces bone growth through the material itself or the addition of bone-inducing factors.
[0003] At present, there are mainly metal, ceramic and degradable polymer types of fracture internal fixation materials. Metal type fracture internal fixation materials have excellent mechanical properties, but the stress shielding effect of metal type fracture internal fixation materials is easy to induce the occurrence of osteoporosis at the fracture site, which may slow down the healing of the fracture. Ceramic type fracture internal fixation materials have the advantage of being gradually converted into natural components in the body, but have the disadvantages of high brittleness, stress concentration and sensitivity to overload, so their use is limited. Currently, the degradable polymer type fracture internal fixation materials on the market are mainly polylactic acid. However, the large amount of lactic acid generated by the decomposition of polylactic acid corrodes bone tissue, so polylactic acid is prone to causing local inflammatory reactions at the repair site. At present, the field still needs to develop fracture internal fixation materials with excellent mechanical properties, good biocompatibility, and a safe and environmentally friendly synthesis process to meet clinical needs.
[0004] Silk protein is a natural polymer fiber protein extracted from silk, which accounts for about 70-80% by weight of silk and contains 18 kinds of amino acids. Silk protein itself has excellent mechanical and physicochemical properties and is highly biocompatible with the human body. Even if silk protein material decomposes in the human body, it produces amino acids and peptides that are non-toxic to the human body. Since most products made from silk fibroin have excellent biocompatibility, silk protein is widely used in the field of biomedical research. However, silk fibroin solution has low solubility in water and is prone to gelation and structural changes when dissolved in a large amount in an organic solvent, so the production of silk fibroin materials places high demands on the manufacturing process.
[0005] Hydroxyapatite (HAP) is the main inorganic component of vertebrate bones and teeth, accounting for about 69 wt% of human bone. Experiments have proven that HAP particles have good biocompatibility and high affinity with bone tissue, and its mineralization liquid can effectively form remineralization deposits and prevent the loss of calcium ions. The addition of hydroxyapatite nanoparticles (nHA) to bone repair products not only improves the mechanical properties of the products, but also improves the biocompatibility of the products. Chinese patent document CN108159501A discloses a method for preparing silk fibroin materials composited with nanoscale material hydroxyapatite, and its use in repairing fracture sites. In this method, nanoscale hydroxyapatite is uniformly dispersed in silk fibroin at a certain ratio, then dissolved in hexafluoroisopropanol, the mixed solution is put into a cylindrical mold and immersed in methanol, so that the silk fibroin molecular chains self-organize to produce a composite material with excellent mechanical strength, and finally the composite material is machined into medical bone nails. However, the silk fibroin material composited with nanoscale material hydroxyapatite described in Chinese patent document CN108159501A is difficult to process into large-sized bone nails. Summary of the Invention
[0006] In response to the problem that conventional silk fibroin / hydroxyapatite composite materials cannot be processed into large-sized bone nails, the present inventors have conducted extensive research and found that the dispersion of hydroxyapatite in large-sized silk fibroin / hydroxyapatite composite materials is not uniform, resulting in insufficient mechanical properties and making it impossible to process the composite materials into large-sized bone nails.
[0007] The technical means provided by the present invention are as follows.
[0008] In the first aspect, (1) incubating a homogeneous mixture of hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol at 50-60°C for at least 3 hours to obtain a viscous silk fibroin / hydroxyapatite solution; (2) placing the silk fibroin / hydroxyapatite solution into a cylindrical mold having two ends, end A and end B; (3) at room temperature, opening end A, sealing end B, immersing the mold vertically in methanol with the opening facing upward, and leaving it still for at least two days; turning the mold upside down, sealing end A, opening end B, immersing the mold vertically in methanol with the opening facing upward, and leaving it still for at least two days; (4) removing the mold and drying through air to obtain a silk fibroin / hydroxyapatite composite material; A method for producing a silk fibroin / hydroxyapatite composite material is provided, comprising:
[0009] Based on the above technical means, a homogeneous mixture is prepared by the following method. (i) Hydroxyapatite nanoparticles and silk fibroin are uniformly mixed and uniformly dispersed in hexafluoroisopropanol, and then incubated at 50-60°C for at least 0.5 hours; (ii) Add hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol in the same proportions as in step (i), mix uniformly, and then incubate at 50-60°C for at least 0.5 hours at least once.
[0010] Preferably, the hydroxyapatite nanoparticles are 25 wt % to 35 wt % based on the total amount of hydroxyapatite nanoparticles and silk fibroin.
[0011] Preferably, the hydroxyapatite nanoparticles are 31 wt % based on the total amount of hydroxyapatite nanoparticles and silk fibroin.
[0012] Preferably, the nanoscale hydroxyapatite has a particle size of 60-80 nm, and the silk fibroin has a particle size of 0.1-1.5 mm.
[0013] Preferably, the incubation temperature in step (1) is 55°C.
[0014] Preferably, the total amount of hydroxyapatite nanoparticles and silk fibroin per 100 mL of hexafluoroisopropanol is 30-40 g.
[0015] In a second aspect, there is provided a silk fibroin / hydroxyapatite composite material produced by the above-mentioned method for producing a silk fibroin / hydroxyapatite composite material. The material can self-degrade into non-toxic substances in vivo, and has biocompatibility and osteoinductivity. Due to its uniformity and morphology, the silk fibroin / hydroxyapatite composite material is formed into a rod of 200 mm length. The rod has excellent mechanical properties and can be processed into a fracture repair component.
[0016] In a third aspect, there is provided a use of the silk fibroin / hydroxyapatite composite in the manufacture of a fracture repair component. Based on the above technical means, the silk fibroin / hydroxyapatite composite is machined to produce a screw with a length of 4-150 mm.
[0017] Specifically, the principle of the present invention is as follows. Hydroxyapatite nanoparticles are highly prone to aggregation in hexafluoroisopropanol, so that hydroxyapatite is dispersed in the silk fibroin / hydroxyapatite composite at a micron scale. In the present invention, the homogeneous mixture of hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol is kept at 50-60°C for at least 1 hour before casting, which ensures that hydroxyapatite is sufficiently dissolved before casting to avoid aggregation or precipitation, and prevents silk fibroin from gelling due to too low temperature, thereby obtaining a silk fibroin / hydroxyapatite solution in which hydroxyapatite nanoparticles and silk fibroin are uniformly dispersed and sufficiently dissolved.
[0018] During the molding process, hydroxyapatite will sink due to gravity, and the distribution in the silk fibroin / hydroxyapatite composite will be uneven, resulting in uneven strength and poor mechanical properties, making it impossible to process into large-sized bone repair parts. In the present invention, the mold is turned upside down during the material molding process, so that the hydroxyapatite will be unevenly distributed in the rod due to gravity, which will prevent the hydroxyapatite from being deposited at one end of the rod and affecting the mechanical properties of the rod.
[0019] In the prior art, it is believed that the components of hydroxyapatite are similar to those of human bone, and can induce the growth of bone cells and promote the recovery of bone defects in patients, but the role of the internal pores of the material in bone induction is not taken into consideration. In the present invention, a long cylindrical mold is used, and the hexafluoroisopropanol in the material is replaced with methanol from top to bottom along the mold to obtain regular internal pores, and after molding a rod, the mold is turned upside down so that methanol enters the mold from the other end, and the hexafluoroisopropanol in the material is replaced from top to bottom, obtaining regular internal pores, in which bone cells can grow, and the bone induction is remarkable.
[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The hydroxyapatite / silk fibroin composite material (nHA / SF) produced by the present invention can be used to produce bone nails with a length of up to 150 mm, with a three-point bending maximum strain stress of 171.73 N and a tensile breaking strength of 112.2 MPa, both of which are significantly higher than those of PLA bone nails with the same specifications, thus resolving the problem that bone nails longer than 4 mm cannot be produced using conventional hydroxyapatite / silk fibroin composite materials. (2) The hydroxyapatite / silk fibroin composite material (nHA / SF) produced by the present invention has pores with a diameter of 2 to 10 μm and regular shape, in which bone cells can grow. As the material decomposes and the bone cells grow, the pores become larger and more bone cells can grow therein, and the composite material has significant osteoinductivity. [Brief description of the drawings]
[0021] In order to more clearly describe the technical means in the embodiments of the present invention, the following briefly introduces the drawings necessary for describing the embodiments. It is obvious that the following drawings are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without creative efforts. [Figure 1] The change trend of the maximum bending strength of silk fibroin / hydroxyapatite composites when the nHA content changes within the range of 0 wt%-40 wt% is shown. [Diagram 2] The change trend of the maximum bending strength of silk fibroin / hydroxyapatite composites when the nHA content changes within the range of 25wt%-35wt% is shown. [Diagram 3] 3 is a photograph of a bar and a bone nail manufactured in Example 1 of the present invention, Fig. 3(A) is the bar, and Fig. 3(B) is the bone nail. [Figure 4] FIG. 2 is a 200x SEM image of the cross section of the silk fibroin / hydroxyapatite composite material obtained in Example 1 of the present invention. [Diagram 5] FIG. 2 is a 2000x SEM image of the cross section of the silk fibroin / hydroxyapatite composite material obtained in Example 1 of the present invention. [Figure 6] FIG. 2 is a 200x SEM image of the cross section of the silk fibroin / hydroxyapatite composite material obtained in Comparative Example 2 of the present invention. [Figure 7] FIG. 2 is a 2000x SEM image of the cross section of the silk fibroin / hydroxyapatite composite material obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] In order to make the purpose, technical means and advantages of the embodiments of the present invention clearer, the technical means of the present invention will be described clearly and completely in the following specific examples. It is obvious that the following examples are only a part of the embodiments of the present invention, and are not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative efforts are all included in the protection scope of the present invention.
[0023] The technical means provided in the embodiments of the present invention are as follows: (1) Take a small amount of silk fibroin powder and mix hydroxyapatite nanoparticles evenly into the silk fibroin powder. Here, the hydroxyapatite nanoparticles are 25wt%~35wt% based on the total amount of hydroxyapatite nanoparticles and silk fibroin. Uniformly disperse the hydroxyapatite nanoparticles and silk fibroin in hexafluoroisopropanol, place in an oven at 50~60℃, and keep warm for 0.5~5h to completely dissolve the hydroxyapatite nanoparticles and silk fibroin. (2) Take out the solution, add equal proportions of hydroxyapatite nanoparticles, silk fibroin powder, and hexafluoroisopropanol, mix uniformly, and then place in an oven at 50-60°C and keep warm for 0.5-5 hours. Repeat the above steps 2-5 times to obtain a sufficient amount of homogeneous hydroxyapatite nanoparticles, silk fibroin powder, and hexafluoroisopropanol. (3) After mixing the homogeneous mixture of hydroxyapatite nanoparticles, silk fibroin powder, and hexafluoroisopropanol, it is subsequently placed in an oven at 50-60°C and baked for 3-24 hours, which ensures that air bubbles are further completely removed and that a homogeneous, viscous silk fibroin / hydroxyapatite solution is obtained. (4) Molding: At 50-60°C, the silk fibroin / hydroxyapatite solution is placed in a specially made cylindrical mold. Both ends of this cylindrical mold are end A and end B, and both ends can be opened. At room temperature, end A is opened and end B is sealed, and the mold is immersed in methanol in a vertical position with the opening facing upwards and left to stand for 2-10 days, during which the hexafluoroisopropanol gradually moves from the opening at the top into the methanol. The mold is turned upside down, end A is sealed, end B is opened, and the mold is immersed in methanol in a vertical position with the opening facing upwards and left to stand for at least 2 days, during which the hexafluoroisopropanol gradually moves from the opening at the top into the methanol. (5) The molded cylindrical solid material is air-dried, and the resulting silk fibroin / hydroxyapatite composite rod is machined.
[0024] In the present invention, the hydroxyapatite nanoparticles and silk fibroin are added multiple times by the method of quantitatively adding small amounts in batches, and are mixed uniformly multiple times in a mixer, so that the hydroxyapatite nanoparticles are uniformly dispersed in the silk fibroin powder before dissolving, and the temperature is maintained at 55°C in the related operations such as casting after dissolving to ensure that the solid is fully dissolved before casting. This series of operations effectively avoids the gelation of silk fibroin, the aggregation and precipitation of hydroxyapatite, and the deterioration of the mechanical properties of the rod due to the uneven distribution of hydroxyapatite caused by low temperature. Only when the gelation of silk fibroin and the aggregation and precipitation of hydroxyapatite do not occur and the mechanical properties are sufficient can the turning device successfully turn the rod into a screw with a length of more than 40 mm. This solves the problem that the conventional silk fibroin / hydroxyapatite composite material cannot process a screw into a large size due to the unevenness of its own material.
[0025] In the present invention, a specially manufactured long cylindrical mold is used in the rod molding process. Both ends of this mold can be opened and closed. The mold is placed vertically in methanol with the opening facing upwards, which ensures that the methanol vertically displaces the hexafluoroisopropanol in the rod from top to bottom. After standing for 2 to 10 days, one end of the rod is almost molded. The mold is turned upside down by 180°, and the methanol enters the mold from the end at the front bottom, and continues to vertically displace the hexafluoroisopropanol in the rod from top to bottom. By this process, the molded rod is a completely vertical and hard rod, and by molding at both ends, the molded rod has uniform density at both the top and bottom ends, and the length of the rod is long. The length of the rod produced by this method can reach up to 150 mm, which can be applied to the production of longer bone nails and meet various clinical needs.
[0026] Unless otherwise specified, the examples and comparative examples of the present invention all use hydroxyapatite nanoparticles with a particle size of 60 nm to 80 nm. The silk fibroin used is all manufactured by the following method. Silkworm cocoons are crushed and pulverized, steamed in a sodium carbonate aqueous solution and degummed for 0.5 hours, the dried silk is dissolved in a 9.3 mol / L lithium bromide solution, the solution is dialyzed with distilled water for 3 days, and then freeze-dried to obtain a white foam-like silk fibroin sample, which is then pulverized in a grinder to a silk fibroin powder with a particle size of 0.25 mm or less.
[0027] Example 1 (1) 5g of silk fibroin powder was taken, hydroxyapatite nanoparticles were added, and the mixture was thoroughly and uniformly mixed using a vortex mixer and an ultrasonic vibrator, where the amount of hydroxyapatite nanoparticles was 0wt%~40wt% relative to the total amount of hydroxyapatite nanoparticles and silk fibroin.
[0028] (2) The homogeneous mixture of hydroxyapatite nanoparticles and silk fibroin powder was uniformly dispersed in hexafluoroisopropanol by adding 35 g of the homogeneous mixture of hydroxyapatite nanoparticles and silk fibroin per 100 mL of hexafluoroisopropanol, and then placed in an oven at 55°C and kept warm for 0.5 h to completely dissolve the hydroxyapatite nanoparticles and silk fibroin powder, and remove air bubbles to obtain a homogeneous mixture of hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol.
[0029] (3) The homogeneous mixture was removed from the oven, and 5 g of silk fibroin powder and the same amount of hydroxyapatite nanoparticles as in step (1) were added thereto and mixed homogeneously. Then, the same amount of hexafluoroisopropanol as in step (2) was added thereto and mixed homogeneously. The mixture was then placed in an oven at 55°C and kept warm for 0.5 hours to obtain a homogeneous mixture of hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol. This step was repeated three times to obtain a sufficient amount of homogeneous mixture that was completely dissolved.
[0030] (4) The homogeneous mixture was placed in an oven at 55°C and then kept at room temperature for 2.5 hours to ensure that the solution was completely homogeneous and that air bubbles were removed, resulting in a viscous and homogeneous silk fibroin / hydroxyapatite solution.
[0031] (5) Molding: In an environment maintained at 55°C, the silk fibroin / hydroxyapatite solution was placed in a specially manufactured long cylindrical mold (made of polypropylene. Both ends of the mold have sealed lids. For ease of explanation, both ends of the mold are called end A and end B, respectively). At room temperature, end A was opened, end B was sealed, and the mold was immersed in methanol in a vertical position with the opening facing upwards and left to stand for 5 days. After that, the mold was turned upside down by 180°, end A was sealed, end B was opened, and the mold was immersed in methanol in a vertical position with the opening facing upwards and left to stand for 5 days.
[0032] (6) The mold was removed, and the molded silk fibroin / hydroxyapatite composite was air-dried and finally machined into a half screw with a specification of 45 mm.
[0033] When the nHA content is 0wt%, the air-dried silk fibroin / hydroxyapatite composite is relatively soft and cannot be successfully processed into threaded products. Figure 1 shows the change trend of the maximum bending strength of the silk fibroin / hydroxyapatite composite when the nHA content changes within the range of 20wt%-40wt%. As shown in Figure 1, when the nHA content is 20wt%, the maximum bending strength of the air-dried silk fibroin / hydroxyapatite composite (SF / HA-20%) reaches 75.38N, when the nHA content is 25wt%, the maximum bending strength of the air-dried silk fibroin / hydroxyapatite composite (SF / HA-25%) is 171.73N, and when the nHA content is 30wt%, the maximum bending strength of the air-dried silk fibroin / hydroxyapatite composite (SF / HA-30%) is 190.21N. That is, the mechanical properties of silk fibroin / hydroxyapatite composites improve with increasing nHA content. However, when the nHA content is 35wt%, the mechanical properties of the air-dried silk fibroin / hydroxyapatite composite (SF / HA-35%) are lower than those of SF / HA-30%, with a maximum bending strength of 180.5N. When the nHA content exceeds 35wt%, the mechanical properties of the silk fibroin / hydroxyapatite composites decrease rapidly, with the maximum bending strength of the silk fibroin / hydroxyapatite composite (SF / HA-40%) with an nHA content of 40wt% being only 82.3N. Analysis suggests that excess nHA aggregates in the SF matrix, resulting in a significant decrease in mechanical properties.
[0034] Based on the above, the inventors further investigated the nHA content and found that when the nHA content was 31 wt%, the maximum bending strength of the air-dried silk fibroin / hydroxyapatite composite (SF / HA-31%) reached an optimal 192.46 N. Figure 2 shows the change trend of the maximum bending strength of the silk fibroin / hydroxyapatite composite when the nHA content was changed within the range of 25 wt% to 35 wt%.
[0035] Next, a turning operation was carried out using the air-dried silk fibroin / hydroxyapatite composite bars manufactured with different ratios of nHA. It was found that when the nHA content was less than 20 wt% or more than 40 wt%, the silk fibroin / hydroxyapatite composite did not have sufficient mechanical properties and could not be used to manufacture large screws with a length of more than 45 mm. However, only the bars in which the hydroxyapatite nanoparticles were 25 wt%-35 wt% of the total amount of hydroxyapatite nanoparticles and silk fibroin could be used to successfully manufacture bone nails with a length of more than 40 mm.
[0036] As shown in Fig. 3(A), the bar material (SF / HA-31%) manufactured in Example 1 has a regular shape, is straight and cylindrical, is easy to process, and can be manufactured into small screws and long full / half screws as needed. The bone nails of two specifications manufactured by processing the bar material (SF / HA-31%) manufactured in Example 1 are abbreviated as SF / HA-31% screws (Fig. 3(B)). Table 1 shows the comparative parameters of the mechanical properties of the SF / HA-31% screws manufactured in Example 1 and commercially available PLA screws.
[0037] Table 1: Comparison of bone nail performance JPEG0007635423000001.jpg40170
[0038] As can be seen from Table 1, the nHA / SF-31% screw with a specification of 45 mm has better mechanical properties than the PLA screw with the same specification.
[0039] Example 2 The rod material (nHA / SF-31%; hydroxyapatite nanoparticles are 31 wt% of the total amount of hydroxyapatite nanoparticles and silk fibroin) prepared in Example 1 was taken and ground into powder, and Fourier transform infrared spectroscopy was used to investigate the mechanism of the enhanced performance of silk fibroin after methanol treatment. -1 , l545cm -1 and 1242 cm -1The absorption peaks at 1634 cm belong to the characteristic absorption peaks of amide I, amide II, and amide III of silk fibroin molecule (Silk), respectively, indicating that its secondary structure is random coil. After regeneration with methanol, the three characteristic peaks are located at 1634 cm -1 , 1520cm -1 and 1230cm -1 , indicating that silk fibroin changes from random coil to β-sheet, which is favorable for increasing the strength of silk fibroin / hydroxyapatite composites. Furthermore, in the infrared spectrum of silk fibroin / hydroxyapatite composites, the peak at 603 cm -1 and 565cm -1 The characteristic absorption at 100 nm corresponds to the OPO bending vibration of phosphate groups, proving the presence of hydroxyapatite in the silk fibroin / hydroxyapatite composites.
[0040] Example 3 The nHA / SF-31% screw prepared in Example 1 was taken and cultured in the ankle bone of a rabbit to follow the decomposition of the nHA / SF-31% screw. As a result, after 2 months of culture in the ankle bone of a rabbit, the gap between the nHA / SF-31% screw and the host bone tissue was significantly reduced, and no inflammatory cells were observed during the decomposition process of the nHA / SF-31% screw, indicating that the decomposition products of the silk fibroin / hydroxyapatite composite material can be absorbed by the human body. Analysis revealed that the decomposition products of the hydroxyapatite / silk fibroin composite material provided by the present invention in the human body are non-toxic and non-irritating products. Specifically, the decomposition products of silk fibroin are amino acids and water that can be absorbed by the human body. Meanwhile, hydroxyapatite is a major component of human bone, and the decomposition products are phosphate ions and calcium ions, both of which are non-toxic and can be excreted from the body by metabolism. Therefore, screws made of hydroxyapatite / silk fibroin composites can completely avoid the risk that PLA screws are prone to cause local inflammation during use.
[0041] Comparative Example 1 This comparative example was similar to Example 1, except that the hydroxyapatite nanoparticles and silk fibroin were dispersed together in hexafluoroisopropanol, and the hydroxyapatite and silk fibroin hexafluoroisopropanol dispersion was not heat treated.
[0042] (1) 5 g of silk fibroin powder was taken, and 2.25 g of hydroxyapatite nanoparticles were added thereto, and the mixture was thoroughly and homogenously mixed using a vortex mixer and an ultrasonic vibrator.
[0043] (2) A homogeneous mixture of hydroxyapatite nanoparticles and silk fibroin powder was uniformly dispersed in 20 mL of hexafluoroisopropanol, and thoroughly mixed homogeneously using a vortex mixer and an ultrasonic vibrator to obtain a hexafluoroisopropanol dispersion of hydroxyapatite and silk fibroin.
[0044] (3) Molding: At room temperature, a hexafluoroisopropanol dispersion of hydroxyapatite and silk fibroin was placed in the mold used in Example 1, end A was opened, end B was sealed, and the mold was immersed in methanol in a vertical position with the opening facing upwards and left to stand for 5 days. After that, the mold was turned upside down by 180°, end A was sealed, end B was opened, and the mold was immersed in methanol in a vertical position with the opening facing upwards and left to stand for 5 days.
[0045] (4) The mold was removed, and the molded silk fibroin / hydroxyapatite composite material was air-dried and finally machined into a half screw with a specification of 45 mm.
[0046] Through experiments, it was found that when the hydroxyapatite nanoparticles were 31wt% relative to the total amount of hydroxyapatite nanoparticles and silk fibroin, the rod material produced in Example 1 was straight and slender, while the rod material produced in Comparative Example 1 was bent during the molding process and had relatively low mechanical properties, so that the rod material broke in the middle during ventilation drying. Analysis showed that in Example 1, the hydroxyapatite nanoparticles could be sufficiently and uniformly mixed and dissolved by multiple mixing and keeping at 55℃, which prevented the hydroxyapatite nanoparticles from agglomerating to the micron scale, thereby avoiding the problem of uneven hydroxyapatite / silk fibroin mixture, while keeping at 55℃ prevented the problem of uneven dispersion of hydroxyapatite due to the gelation of silk fibroin at low temperature.
[0047] Comparative Example 2 This comparative example was similar to Example 1, except that a conventional mold was used that was open only at one end and had a relatively large diameter.
[0048] (1) 5 g of silk fibroin powder was taken, and 2.25 g of hydroxyapatite nanoparticles were added thereto, and the mixture was thoroughly and homogenously mixed using a vortex mixer and an ultrasonic vibrator.
[0049] (2) The homogeneous mixture of 7.25 g of hydroxyapatite nanoparticles and silk fibroin powder obtained in step (1) was uniformly dispersed in 20 mL of hexafluoroisopropanol, and then placed in an oven at 55°C for 0.5 h to completely dissolve the hydroxyapatite nanoparticles and silk fibroin powder, remove air bubbles, and obtain a homogeneous mixture of hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol.
[0050] (3) The homogeneous mixture of hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol was removed from the oven, and 5 g of silk fibroin powder and 2.25 g of hydroxyapatite nanoparticles were added thereto and mixed homogeneously. Then, 20 mL of hexafluoroisopropanol was added thereto and mixed homogeneously. The mixture was then placed in a 55°C oven and kept warm for 0.5 h to obtain a homogeneous mixture of hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol. This step was repeated three times to obtain a sufficient amount of homogeneous mixture that was completely dissolved.
[0051] (4) The homogeneous mixture was placed in an oven at 55°C and then kept at room temperature for 2.5 hours to ensure that the solution after homogeneous mixing was completely homogeneous and that air bubbles were removed, resulting in a viscous and homogeneous silk fibroin / hydroxyapatite solution.
[0052] (5) Molding: The silk fibroin / hydroxyapatite solution was poured into a conventional mold at 55° C. The conventional mold was immersed in methanol at room temperature with the opening facing upwards and left to stand for 10 days.
[0053] (6) The mold was removed, and the molded silk fibroin / hydroxyapatite composite was air-dried to obtain a rod, which was finally machined into a half screw.
[0054] The rods produced in Example 1, in which the hydroxyapatite nanoparticles are 31 wt% relative to the total amount of the hydroxyapatite nanoparticles and silk fibroin, and the rods produced in Comparative Example 2 were taken, cut at 2 mm, and two groups of sections were photographed using a scanning electron microscope at 200x and 2000x magnification, respectively. FIG. 4 shows an SEM image of a cross section of the rod produced in Example 1 at 200x magnification, and it was observed that many vertical pores were uniformly distributed in the rod. FIG. 5 shows an SEM image of a cross section of the rod produced in Example 1 at 2000x magnification. As can be seen from FIG. 5, the diameter of the vertical pores in the rod was 2-10 μm, and the part without pores was flat. The size of the pores is close to that of human cells, which is favorable for bone cells to grow therein and can promote the growth of bone cells. With the decomposition of the material and the growth of bone cells, the pores become even larger, and more bone cells can grow therein, so this rod has osteoinductivity. FIG. 6 shows a 200x SEM image of the cross section (with the screw head facing vertically downward) of the bar produced in Comparative Example 2. As can be seen from the figure, the pore distribution in the cross section of the bar produced in Comparative Example 2 is not regular but uneven, and no pores can be observed in many parts. FIG. 7 shows a 2000x SEM image of the cross section (with the screw head facing vertically downward) of the bar produced in Comparative Example 2. As can be seen from FIG. 7, the pores in this bar are very few and uneven, making it difficult to induce the growth of bone cells with this structure. Therefore, this bar does not have osteoinductivity. Analysis showed that in Example 1, when the rod was being molded, methanol entered the material from end A of the mold and replaced the hexafluoroisopropanol in the material from top to bottom, resulting in relatively regular internal pores; after the rod was almost completely molded, it was turned upside down, whereupon methanol entered the material from end B of the mold and replaced the hexafluoroisopropanol in the rod from top to bottom, resulting in a regular and uniform structure of the rod as a whole.On the other hand, in Comparative Example 2, when the rod is molded, methanol can only penetrate into the material from the upper end opening of the mold, and cannot penetrate to the bottom end of the long mold to replace the hexafluoroisopropanol in the material, so when a relatively long rod is manufactured, the upper and lower ends of the rod are not molded uniformly, and the molded rod is difficult to screw successfully, resulting in a huge waste of material. In addition, since the conventional mold has a large diameter, molding is not performed completely from top to bottom, and after methanol enters the material, it diffuses randomly in the horizontal direction to replace the hexafluoroisopropanol, so the internal pores of the molded rod are not regular and are not suitable for the growth of bone cells. From the above, in the present invention, by using a long cylindrical mold that can be opened at both ends and a molding process of upside down, the rod has more regular internal pores, and cells can grow in these internal pores, which improves its biocompatibility and creates osteoinductivity.
[0055] The above description is merely specific embodiments of the present invention for those skilled in the art to understand or realize the present invention. Various modifications to these embodiments will be obvious to those skilled in the art. The general principles defined in this specification can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is limited to these embodiments shown in this specification and should be accorded the widest scope consistent with the principles and novel features claimed in this specification.
Claims
1. (1) incubating a homogeneous mixture of hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol at 50-60° C. for at least 3 hours to obtain a viscous silk fibroin / hydroxyapatite solution; (2) placing the silk fibroin / hydroxyapatite solution into a cylindrical mold having two ends, end A and end B; (3) at room temperature, opening the A end, sealing the B end, immersing the mold vertically in methanol with the opening facing upward, and leaving it still for at least two days; turning the mold upside down, sealing the A end, opening the B end, immersing the mold vertically in methanol with the opening facing upward, and leaving it still for at least two days; (4) removing the mold and drying the mold to obtain a silk fibroin / hydroxyapatite composite material; Including, A method for producing a silk fibroin / hydroxyapatite composite material, wherein the hydroxyapatite nanoparticles are 25 wt %-35 wt % based on the total amount of the hydroxyapatite nanoparticles and the silk fibroin.
2. The homogeneous mixture comprises: (i) homogeneously mixing hydroxyapatite nanoparticles and silk fibroin, dispersing homogeneously in hexafluoroisopropanol, and incubating at 50-60° C. for at least 0.5 hours; (ii) adding hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol in the same proportion as in step (i), mixing uniformly, and then incubating at 50-60°C for at least 0.5 hours at least once; The method for producing the silk fibroin / hydroxyapatite composite material according to claim 1, characterized in that it is produced by a method comprising the steps of:
3. The method for producing silk fibroin / hydroxyapatite composite material according to claim 1, characterized in that the hydroxyapatite nanoparticles are 31 wt% based on the total amount of the hydroxyapatite nanoparticles and silk fibroin.
4. The method for producing silk fibroin / hydroxyapatite composite material according to claim 1 or 2, characterized in that the particle size of the nanoscale hydroxyapatite is 60-80 nm, and the particle size of the silk fibroin is 0.1-1.5 mm.
5. The method for producing silk fibroin / hydroxyapatite composite material according to claim 1 or 2, characterized in that the incubation temperature in step (1) is 55°C.
6. The method for preparing silk fibroin / hydroxyapatite composite material according to claim 1 or 2, characterized in that the total amount of hydroxyapatite nanoparticles and silk fibroin added per 100mL hexafluoroisopropanol is 30-40g.
Citation Information
Patent Citations
Silk protein dental implant and preparation method thereof
CN106667595A
A silk fibroin bone nail and a preparing method thereof
CN107041972A
Preparation method of silk fibroin material of composite nano-grade hydroxyapatite and application of silk fibroin material in repairing bone fracture parts
CN108159501A
3D Silk Hydroxyapatite Composition
JP2011511668A
Three-dimensional silk hydroxyapatite composition
JP2015205208A